Why are teachers afraid of curricular autonomy? Contradictory effects of the new national curriculum in South Korea. (15th January 2016) - Hong, Won-Pyo; Youngs, Peter
Abstract : Using interview data from secondary teachers, this study examines conflicting perspectives on the effects of the new national curriculum in South Korea, which was intended to grant more autonomy to individual schools and teachers. Contrary to the general belief that teachers want more autonomy to customize their curricula to meet students' needs, this study found that the participating teachers did not welcome the enhanced curricular autonomy nor did they believe it would diversify the school curriculum. The primary causes of this contradiction are the gap between the desired and the granted autonomy, the new national curriculum's negative impact on the relationships among teachers and their job security, and the prevalent credential culture in South Korea. Based on these findings, this study suggests wider implications for curriculum scholars and policymakers in other contexts concerning the nature and effects of teacher autonomy in curriculum development.